The Effect Of Physical Activity Level In Body Mass Index During The New Normal Period - Saharuddin Ita; Ipa Sari Kardi; Baharuddin Hasan; Dewi Nurhidayah (JUARA : Jurnal Olahraga, 2022)
The level of physical activity is one indicator of whether a person is active. This study aims to see the effect of physical activity level on body mass index. The method used in this study is the correlational method which aims to detect the level of physical activity on body mass index during the new normal period. The population in this study were all FIK Cenderawasih University students totalling 387 students. Determined the sample using a simple random sampling technique to obtain a sample of 97 students aged 19 – 24 years consisting of 61 men and 36 women. The data collection technique used the International Physical Activity Questionnaire (IPAQ) instrument to measure the level of physical activity and anthropometric measurements of the body to obtain BMI values. The data analysis results showed that students' physical activity level was dominant in the high category 54.6%, the medium category 30.9%, and the low category 14.4%, besides that. There were differences between the activity levels of males and females. The average level of physical activity for men is in the high category, and the average for women is in the medium category. The study's results found a positive effect of physical activity on the BMI of FIK Cenderawasih University students during the new average period.